PENGELOLAAN DAN PEMANFAATAN DAERAH ALIRAN SUNGAI CISANGGARUNG SEBAGAI POTENSI SUMBER DAYA ALAM DI DESA LURAGUNGLANDEUH DAN DESA CIKEUSAL - Alpiyah, Lilis Nur; Fajri, Hikma Mudia; Hidayati, Nurul; Zalilla, Zillan; Zulfikar, Ismail; Abdi, Ansar (Faculty of Forestry and Environment, Universitas Kuningan, 2024)
The purpose of writing this article is to provide an overview of the profile of the Luragunglandeuh Village and Cikeusal Village areas in the Watershed. Watershed management is one of the natural resources that is so complex and consists of several components that make it up. These components consist of vegetation resources (forests), soil and water (rivers and tributaries), and humans contained in the area as users of space and natural resources contained therein. Where the upstream watershed ecosystem has a very close relationship with the downstream watershed ecosystem. Natural resources are all wealth in the form of inanimate and living objects found on earth that can be utilized to meet human needs. The pressure on natural resources is very large along with human guidance to meet the needs of life. Humans are highly dependent on natural resources and the sustainability of natural resources is greatly influenced by human activities. Natural resources in Luragunglandeuh Village and Cikeusal Village are in the form of agricultural and plantation sectors. Das Cisanggarung in Luragung and Cikeusal has the potential to support life for the surrounding community such as the use of clean water for agricultural development, household life and the livelihood of the surrounding community.